Results from a magnetic survey & geomagnetic depth sounding in the post eruption phase of the Barren Island volcano - Banerjee, B.; Subbarao, P.B.V.; Gupta, Gautam; Joseph, E.J.; Singh, B.P. (My University, 1998)
The Geological Survey of India conducted a magnetic survey and geological studies in 1993 around Barren Island in the Andaman Sea on board the RV Samudra Manthan. Five ocean bottom magnetometers were deployed by the Indian Institute of Geomagnetism as a part of this cruise. The Curie isotherm profiles prepared from the seasurface magnetic data indicate a high heat flow in the east of Barren Island. These profiles also indicate the presence of a north-south structural barrier which has prevented upflow of volcanic material to the west of Barren Island. Ocean-bottom magnetometer data were recorded simultaneously at five sites for about 15 days and these have been used to determine the electrical conductivity structure beneath Barren Island. Magnetic variations recorded at the seafloor stations indicate a concentration of electric currents near the island instead of the usual effect where currents are deflected away from the island. Transfer functions, showing the relationship between the horizontal components of the seafloor stations and land station, have been computed and the quantitative estimates of the transfer functions across Barren Island indicate a high conducting zone at a depth of about 17–27 km. This zone may have been produced by an upwelling of the mantle material through the magma chamber. The structure of this conductive zone at the north and south of Barren Island seems to concentrate the flow of the subsurface electrical currents within the island and the current flow takes a sharp southward turn beneath the island. This north-south conducting zone may have caused a rise in the depth of the Curie isotherm mapped by a shipborne magnetic survey of this region. Most probably, a partial melting of this conductive zone (magma chamber) may have given rise to the volcanic activity on Barren Island.
Keywords: Magnetic variations; Barren island; Curie isotherm; Geomagnetic depth sounding